2021
DOI: 10.1111/and.14310
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin 3‐gallate improves the quality of bull semen cryopreservation

Abstract: To determine the effects of epigallocatechin-3-gallate (EGCG) on the cryopreservation of bovine semen, epigallocatechin-3-gallate dissolved with double distilled water to 0.2, 0.4, 0.6 and 0.8 mg/ml were added to the cryopreservation diluent of the bull semen. Then, we used computer-assisted analysis of semen kinematic parameters, staining method to detect membrane function, acrosome integrity, enzyme-linked immunosorbent assay to detect catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GSH-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Among these studies, it was reported that the 200 and 300 μM supplementation of epigallocatechin gallate had a positive effect on total and progressive motility in buffalo bulls (Ahmed et al, 2020). In another study, in which different doses of epigallocatechin 3‐gallate were tested in bull semen freezing, it was revealed that a dose of 0.6 mg/L epigallocatechin 3‐gallate application increased total motility, and it had enhancing effects on VAP, VCL and VSL (Li et al, 2022). In a study on stallions, it was stated that resveratrol and epigallocatechin‐3‐gallate had favourable effects on motility, viability and HMMP (Nouri et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these studies, it was reported that the 200 and 300 μM supplementation of epigallocatechin gallate had a positive effect on total and progressive motility in buffalo bulls (Ahmed et al, 2020). In another study, in which different doses of epigallocatechin 3‐gallate were tested in bull semen freezing, it was revealed that a dose of 0.6 mg/L epigallocatechin 3‐gallate application increased total motility, and it had enhancing effects on VAP, VCL and VSL (Li et al, 2022). In a study on stallions, it was stated that resveratrol and epigallocatechin‐3‐gallate had favourable effects on motility, viability and HMMP (Nouri et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The technology of the cryopreservation of semen obtained from rams with high breeding value not only enables the use of semen beyond international borders but also plays a key role in sheep breeding (Li et al, 2022). Although it has many advantages, ice crystals formed during the freezing process of semen, biochemical and cellular changes induced by these crystals in spermatozoa after thawing, possible negative developments on sperm morphology and motility (Peris‐Frau et al, 2020), and damage to the plasma membrane and DNA integrity (Taşdemir et al, 2013) are some disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…The activities of MDA and CAT are also the main indicators that reflect the body's antioxidant level. 49 Therefore, this study used the determination of the content of MDA and the activities of GSH-Px, CAT, and SOD activity as important indicators to reflect the effect of drugs. The results show that BA LCH NPs can effectively increase the activities of GSH-Px, CAT, and SOD activity and reduce the level of MDA and showed good antioxidant effects.…”
Section: Discussionmentioning
confidence: 99%
“…BA may mainly increase the activities of GSH-Px, CAT, and MDA levels so as to eliminate the effect of reactive oxygen of in the lens. , GSH-Px is a strong reducing agent with a high content in the lens, which can inhibit the formation of disulfide bonds of protein sulfhydryl groups and play a multifaceted regulatory role on the lens. The activities of MDA and CAT are also the main indicators that reflect the body’s antioxidant level . Therefore, this study used the determination of the content of MDA and the activities of GSH-Px, CAT, and SOD activity as important indicators to reflect the effect of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In the NPS GTE, the content of Epigallocatechin Gallate (EGCG) in GTE has a high antioxidant effect that captures free radical scavenging, superoxide anion, and peroxy radicals, terminating the lipid peroxidation chain (Zhang et al, 2021), and phosphorylation of AMPK (Saeki et al, 2018). The supplementation of EGCG in the extender of frozen semen increases post-thawing sperm motility of buffalo (Ahmed et al, 2020), and bovine spermatozoa (Li et al, 2022). Sperm motility is the primary indicator of post-thawed semen quality (INSA, 2014), and it is correlated to MDA, IPM viability and SDF (Susilowati et al, 2022).…”
Section: Discussionmentioning
confidence: 99%